Development of Quality Tungsten Coating on Ceramics as a Microwave Shield for ITER High-Frequency Magnetic Sensor. (2nd January 2020) - Begrambekov, L.; Gordeev, A.; Ma, Y.; Vayakis, G.; Shigin, P.; Sadovsky, Ya; Zakharov, A.; Walsh, M.
Abstract: High-quality tungsten coating deposition on sintered aluminum nitride ceramic substrates (both of thin flat chips and structural boxes) was realized using an adapted plasma-aided coating deposition rig. The tungsten coating produced using this technique and the accompanying apparatus setup are of high-purity, strong adhesion, and controlled three-dimensional uniformity (<20% thickness variations). The coating also exhibits well-structured and smooth (Ra < 1.0 µm) microscopic surface landscape with densely clustered tungsten granulations. The coated samples were tested under load conditions expected during ITER operation, including thermal cycling and superheated (up to 500°C) steam. Exposure to thermal cycles and hot steam made no apparent changes to the coating's microscopic structure with no sign of cracks, blistering, or exfoliation seen under electron microscopy. These successes validated the microwave shield design for the ITER high-frequency magnetic sensor, which is based on this concept, and laid a solid foundation for the production of this component in the forthcoming procurement phase. Besides, a failure test was conducted for the tungsten coating in the temperature range of 500°C to 1500°C. Surface smoothing, pores, delamination, and mass loss in substrate were observed when temperature exceeded 1000°C, possibly due to the evaporation of aluminum atoms. These findings unveiled the changes of tungsten coating properties under extreme conditions that are of both academic and practical values.